Rationale and practical recommendations for testing protocols in female soccer: a narrative review - Beato, M.; Datson, N.; Anderson, L.; Brownlee, T.; Coates, A.; Hulton, A. (The Journal of Strength and Conditioning Research, 2023)
The aim of this narrative review is to evaluate the presented literature on tests (aerobic, speed, changes of direction [COD], strength, power, jump, and anthropometry) of the varied components of female soccer and to draw attention to the most suitable protocols to allow practitioners to accurately track players' fitness status. The 2 most common field tests used to assess aerobic fitness are the Yo-Yo intermittent test (level 1 and level 2) and the 30-15 intermittent fitness test because of an ability to measure multiple players at once with a soccer-specific intermittent profile. The sprinting performance can be assessed on distances of <30 m; however, longer distances (e.g., 40 m) allow for achieving peak speed (flying sprint test), which can be assessed using global navigation satellite system. Changes-of-direction capacity has been found to be an important component of players testing and training programs, although there is no "gold standard" to assess COD or repeated sprint ability performance in female players. Lower-limb power can be assessed using jump tests that can use force platforms, jump mats, and optoelectronic devices, while maintaining a good reliability. Several in-direct tests are currently available for assessing anthropometry parameters, such as skinfold thickness, hydrodensitometry, and ultrasound. However, dual-energy x-ray absorptiometry is the most valid and reliable method for assessing body composition in team sport athletes, with the addition of bone health that is a key measure in female athletes. In conclusion, the evidence reported in this review will be able to aid practitioners, coaches, and researchers to decide which tests meet the requirements of their environment.